40Ar/39Ar ages and geochemistry of the Intersalar Range of the Bolivian Altiplano: A volcanological transect spanning the arc and reararc of the Central Andean Plateau - Salisbury, Morgan J.; Jiménez, Néstor; Barfod, Dan (Frontiers in Earth Science, 2022)
The volcanic Intersalar Range of western Bolivia provides a unique opportunity to examine geochemical variations spanning the arc and reararc regions of the Central Andean Plateau. In this study we report 23 new 40Ar/39Ar ages, 15 whole-rock Sr-Nd-Pb isotope analyses, and 50 whole-rock major and trace element analyses from samples collected across ∼115 km of the Intersalar Range. Most samples are classified as trachyandesites and trachydacites, with the most mafic lavas (slightly alkaline, basaltic trachyandesites) erupting from the Pliocene Coracora volcano in the central Altiplano. We identify two distinct pulses of reararc magmatism: a Miocene phase between 20 Ma and 14 Ma that corresponds with local compressional shortening, and a Plio-Pleistocene phase between 5 and 1 Ma that postdates observed structural deformation in the region. 87Sr/86Sr values (0.70512–0.70600) and 143Nd/144Nd values (0.51226–0.51255) are generally higher, and lower, respectively, in the younger phase, whereas Pb isotopes (206Pb/204Pb = 17.7315–18.5095; 207Pb/204Pb = 15.5714–15.6279; 208Pb/204Pb = 37.7862–38.6156) show little variation with age. Isotope values are only loosely correlated with distance from the modern Central Volcanic Zone. Higher Sr/Y, Dy/Yb, and [La/Yb]N values in the Plio-Pleistocene samples are consistent with homogenization at the base of a thicker continental crust compared to the Miocene samples. Nb concentrations show the strongest correlation with distance into the reararc compared to all other trace elements (arc Nb = 6–16 ppm; reararc Nb = 12–26 ppm). Nb/Nb* values (a measurement of the depth of the negative Nb anomaly) correspondingly increase into the reararc (indicating smaller anomalies), reaching a maximum at Coracora volcano before decreasing in the far rear arc region. Compiled data across the Central Andean Plateau reveal a strong correlation between Nb/Nb* and the presence of intact mantle lithosphere beneath the central Altiplano. We interpret this distinct Nb signal to reflect melting triggered by the breakdown of Nb-rich hydrous minerals within foundering (delaminating) mantle lithosphere. In conjunction with spatiotemporal data, Nb systematics provide the clearest indication of mantle lithosphere in regions where mafic samples are not present.